Analysis of the operation of on farm emergency slaughter of bovine animals in the Republic of Ireland. Issue 1 (December 2015) - McDermott, Paul; McKevitt, Aideen
Abstract Background On Farm Emergency Slaughter (OFES) is the slaughter outside the slaughterhouse, of an otherwise healthy animal, which has suffered an accident that, for welfare reasons, prevented its transport to a slaughterhouse. The procedure is designed to prevent the transport of welfare compromised animals, which may have veterinary certification to slaughterhouses for Casualty Slaughter (CS), and provides an alternative to the euthanasia and disposal of injured animals that are otherwise fit for human consumption. The aim of this study was to analyse the operation of OFES in the Republic of Ireland between 1st January 2011 and 31st December 2013. Methods Data were obtained from the Animal Identification and Movement electronic database of the Department of Agriculture, Food and the Marine. Two structured surveys were designed, one for Official Veterinarians (OVs) who work in slaughterhouses and the second for Private Veterinary Practitioners (PVPs) who work in food animal practice in the Republic of Ireland. Surveys were administered throughSurveyMonkey . The total number of bovines slaughtered and the number that underwent OFES in Northern Ireland and the Netherlands were obtained from the Northern Ireland Department of Agriculture and Rural Development and the Netherlands Food and Consumer Safety Authority. Results OFES is neither widely available nor used in the Republic of Ireland. Results from the OV survey showed that Food Business Operators consider that facilitation of OFES would be detrimental to business. Data from the 5 slaughterhouses which offer OFES showed that acceptance criteria are not standardised. Results from the PVP survey showed that 77 % (n  = 79) of PVPs were willing to certify animals for OFES. Fifty four percent (n  = 49) were aware of slaughterhouses in their area that provided the service of OFES and 64 % (n  = 57) stated a willingness to certify the transport of acutely injured animals to slaughterhouses for CS. Data from the Northern Ireland Department of Agriculture and Rural Development and the Netherlands Food and Consumer Safety Authority indicated a low level of uptake of OFES in the Republic of Ireland compared to Northern Ireland and the Netherlands. Conclusion Based on results reported here, criteria for assessment of risk associated with accepting animals for OFES should be reconsidered. A review of the systems pertaining to OFES and its implementation should be undertaken, including the level and quality of training of all stakeholders, with a view to making OFES more widely available in the Republic of Ireland.